Pembinaan Kepribadian dan Kemandirian Narapidana dalam Lembaga Pemasyarakatan (Studi pada Lembaga Pemasyarakatan Kelas II Jombang) - Heppy Hyma Puspitasari; Muslimin Muslimin (IKIP Budi Utomo Malang, 2022)
People who violate the applicable legal provisions will receive sanctions. sanctions can be in the form of social sanctions, for example being ostracized by the surrounding community, other sanctions can be in the form of imprisonment or punishment. Punishment or imprisonment is carried out in Correctional Institutions. Penitentiary or commonly abbreviated as LP or Lapas is a place to provide guidance to prisoners and correctional students in Indonesia. Correctional institutions are not only to punish people who commit crimes but also as an effort to correct prisoners. Correctional institutions have a very important role in terms of providing guidance to prisoners. Coaching is carried out in accordance with standard rules. Coaching can be done through personality development and independence development. With coaching carried out by correctional institutions, it is hoped that it will be able to help convicts to return to society after serving their sentence. The focus of the research is how to implement independence coaching for prisoners in Class II B Correctional Institutions in Jombang and how the obstacles experienced by correctional institutions in implementing coaching. This study uses qualitative research. Qualitative research is a research method that is based on the philosophy of postpositivism, used to research on natural object conditions, where the researcher is the key instrument, so the researcher must have theoretical provisions and broad insights, so as to be able to ask questions, analyze, photograph and construct social situations that research becomes clear and meaningful. The result of the research is that personality development for prisoners in class II prisons in Jombang is carried out by carrying out worship according to their religion and beliefs. There is a place of worship for the convicts. Self-reliance development is carried out by providing training at work workshops and landscaping, in the furniture workshop convicts carry out furniture activities including making bird cages, ship miniatures, and making study tables. landscaping activities for convicts cleaning gardens, arranging gardens and providing guidance on the development of vegetable nurseries.